Sosialisasi Bahaya Penyalahgunaan Narkoba Bagi Peserta Didik SMP Negeri 4 Kwandang Kabupaten Gorontalo Utara - Herinda Mardin; Hariana Hariana; Trifandi Lasalewo (Universitas Negeri Gorontalo, 2022)
The purpose of the socialization activity on the dangers of drug abuse in Junior High School (SMP) Negeri 4 Kwandang, North Gorontalo Regency is so that participants can understand the impact of drug use, both physical, psychological and socio-economic impacts. Socialization activities use participatory methods, lectures and discussions. The socialization activity was carried out on October 12, 2021 with the number of participants who took part in the socialization activity consisting of 25 students and 10 teachers located in the hall of SMP Negeri 4 Kwandang. For this reason, through socialization activities on the dangers of drug abuse, it is able to increase the understanding of students of SMP Negeri 4 Kwandang about the types of narcotics, the impact of drug abuse from the physical, psychological, educational, social and economic aspects as well as ways to prevent and overcome drug abuse among children and teenager. For this reason, this socialization activity can fortify the younger generation as the nation's next generation, especially students at SMP Negeri 4 Kwandang, North Gorontalo Regency from the dangers of drug abuse.